Men at work: Labourers and building craftsmen in the towns of northern England, 1450-1750 - Levine, David (Labour / Le Travail, 1998)
The article reviews the book, "Men at work: Labourers and building craftsmen in the towns of northern England, 1450-1750," by Dbnald Woodward.

London in the Age of Industrialisation: Entrepreneurs, Labour Force and Living Conditions, 1700-1850 - Levine, David (Labour / Le Travail, 1994)
The article reviews the book, "London in the Age of Industrialisation: Entrepreneurs, Labour Force and Living Conditions, 1700-1850," by L. D. Schwarz.
Keywords: BOOKS -- Reviews; LABOR supply; LONDON in the Age of Industrialisation: Entrepreneurs, Labour Force & Living Conditions 1700-1850 (Book); Nonfiction; SCHWARZ, L. D.

Class Formation and Urban-Industrial Society: Bradford, 1750-1850 - Levine, David (Labour / Le Travail, 1992)
The article reviews the book, "Class Formation and Urban-Industrial Society: Bradford, 1750-1850," by Theodore Koditschek.
Keywords: BOOKS -- Reviews; CLASS Formation & Urban Industrial Society: Bradford 1750-1850 (Book); Class formation; KODITSCHEK, Theodore; Nonfiction

The Great War and the British People - Levine, David (Labour / Le Travail, 1988)
This article reviews the book, "The Great War and the British People," by J. M. Winter.
Keywords: GREAT War & the British People, The (Book); Nonfiction; REVIEWS; WAR & society; WINTER, J. M.; books

The Great Arch: English State Formation as Cultural Revolution - Levine, David (Labour / Le Travail, 1987)
This article reviews the book, "The Great Arch: English State Formation as Cultural Revolution," by Philip Corrigan and Derek Sayer.

The History of the British Coal Industry. Volume 2: 1700-1830, The Industrial Revolution - Levine, David (Labour / Le Travail, 1986)
This article reviews the book, "The History of the British Coal Industry. Volume 2: 1700-1830, The Industrial Revolution," by Michael W. Flinn assisted by David Stoker.
Keywords: COAL industry -- History; FLINN, Michael W.; HISTORY of the British Coal Industry 1700-1830: The Industrial Revolution, The (Book); Nonfiction; REVIEWS; books

Malthus Past and Present - Levine, David (Labour / Le Travail, 1986)
This article reviews the book, "Malthus Past and Present," edited by J. Dupaquier, A. Fauve-Chamoux & E. Grebcntk.

Under the Skin of English Life - Levine, David (Labour / Le Travail, 1984)
The article reviews and comments on "The Question of Class Struggle: Social Foundations of Radicalism During the Industrial Revolution," by Craig Calhoun, "Work, Society and Politics: The Culture of the Factory in Later Victorian England," by Patrick Joyce, and "English Culture and the Decline of the Industrial Spirit 1850-1980," by Martin Wiener.

The Agrarian History of England and Wales: Volume V. Part 1: Regional Farming Systems; Part 2: Agrarian Change - Levine, David (Labour / Le Travail, 1988)
The article reviews the book, "The Agrarian History of England and Wales: Volume V. Part 1: Regional Farming Systems; Part 2: Agrarian Change," edited by Joan Thirsk.